Association between serum total cholesterol levels and Crohn’s clinical disease severity: a retrospective cross-sectional study - Ni, Jinchun; Tang, Yunna; Zhou, Fangyuan; Hu, Yiqun; Liu, Lupeng; Huang, Mingcheng; Ouyang, Hui; Xie, Chenxi (Frontiers in Medicine, 2025)
BackgroundThis retrospective cross-sectional study aimed to investigate the relationship between serum total cholesterol (TC) levels and the clinical activity of Crohn’s disease (CD).MethodsOne hundred and four patients with Crohn’s disease (CD) and twenty healthy volunteers were included in the analysis. Serum uric acid (SUA) levels and indicators related to lipid metabolism were measured within 1 week before undergoing endoscopic and CT enterography (CTE) examinations. Patients were divided into groups based on their Crohn’s Disease Activity Index (CDAI) scores.ResultsPatients were categorized into mild and moderate groups, with no patients meeting the criteria for severe CD. The serum uric acid (SUA) and triglyceride (TG) levels were similar between CD patients and the control group (p > 0.05). However, the levels of total cholesterol (TC), apolipoprotein A1 (apo A1), apolipoprotein B (apo B), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) were higher in the control group (p < 0.05). The TC and LDL-C levels were lower in the moderate patients compared to those in mild group (p < 0.05). TC ≤ 3.5 mmol/L was identified as an independent risk factor for more severe disease (OR = 4.50, 95%CI 1.612–12.561, p = 0.004). TC levels were correlated to both CRP and CDAI scores negatively (p < 0.05).ConclusionTC may serve as a potential supplementary marker for clinical disease activity in CD, but further research, including longitudinal studies, is needed to confirm its reliability.